2011
DOI: 10.1152/japplphysiol.00852.2010
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol's beneficial effect on murine muscle function is independent of muscle activity

Abstract: Estradiol (E₂) deficiency decreases muscle strength and wheel running in female mice. It is not known if the muscle weakness results directly from the loss of E₂ or indirectly from mice becoming relatively inactive with presumably diminished muscle activity. The first aim of this study was to determine if cage activities of ovariectomized mice with and without E₂ treatment differ. Ovariectomized mice were 19-46% less active than E₂-replaced mice in terms of ambulation, jumping, and time spent being active (P ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
61
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 37 publications
4
61
2
Order By: Relevance
“…Our results also indicate that E 2 works through specific kinase signaling pathways involving ER␤ and GPER. These data extend previous reports of E 2 affecting skeletal muscle force generation (16,38,39,43,66) and provide insight into a specific molecular modification of myosin as an underlying mechanism. E 2 , as well as the estrogenic compound genistein, has previously been shown to enhance pRLC in other cell types including mouse cardiac muscle (24,54).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results also indicate that E 2 works through specific kinase signaling pathways involving ER␤ and GPER. These data extend previous reports of E 2 affecting skeletal muscle force generation (16,38,39,43,66) and provide insight into a specific molecular modification of myosin as an underlying mechanism. E 2 , as well as the estrogenic compound genistein, has previously been shown to enhance pRLC in other cell types including mouse cardiac muscle (24,54).…”
Section: Discussionsupporting
confidence: 89%
“…with sham-operated mice (16,38,39,53,65). It was suggested (41) and subsequently demonstrated that ovarian hormones influence muscle strength by directly affecting the function of contractile proteins (43,66), particularly the structure and function of myosin (38,39).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Physical activity Twenty-four-hour cage activity was assessed using open field activity chambers (Med Associates Inc., St. Albans, VT) (Greising et al 2011). Briefly, chambers contain infrared arrays in the x-, y-, and z-axes with two sets of beams in the x-direction, one being elevated to 2.5 or 5.4 cm above the bottom of the cage for Zmpste24 −/− and Zmpste24 +/+ mice, respectively (to account for their body size differences).…”
Section: Methodsmentioning
confidence: 99%